Phosphorus Inventory for the Conterminous United States (2002–2012). Issue 4 (6th April 2021) - Sabo, Robert D.; Clark, Christopher M.; Gibbs, David A.; Metson, Geneviève S.; Todd, M. Jason; LeDuc, Stephen D.; Greiner, Diana; Fry, Meridith M.; Polinsky, Robyn; Yang, Qichun; Tian, Hanqin; Compton, Jana E.
Abstract: Published reports suggest efforts designed to prevent the occurrence of harmful algal blooms and hypoxia by reducing non‐point and point source phosphorus (P) pollution are not delivering water quality improvements in many areas. Part of the uncertainty in evaluating watershed responses to management practices is the lack of standardized estimates of phosphorus inputs and outputs. To assess P trends across the conterminous United States, we compiled an inventory using publicly available datasets of agricultural P fluxes, atmospheric P deposition, human P demand and waste, and point source discharges for 2002, 2007, and 2012 at the scale of the 8‐digit Hydrologic Unit Code subbasin (∼1, 800 km 2 ). Estimates of agricultural legacy P surplus accumulated from 1945 to 2001 were also developed. Fertilizer and manure inputs were found to exceed crop removal rates by up to 50% in many agricultural regions. This excess in inputs has led to the continued accumulation of legacy P in agricultural lands. Atmospheric P deposition increased throughout the Rockies, potentially contributing to reported increases in surface water P concentrations in undisturbed watersheds. In some urban areas, P fluxes associated with human waste and non‐farm fertilizer use has declined despite population growth, likely due, in part, to various sales bans on P‐containing detergents and fertilizers. Although regions and individual subbasins have different contemporary and legacy P sources, a standardized method of accounting for large and small fluxes and ready to use inventory numbers provide essential infromation to coordinate targeted interventions to reduce P concentrations in the nation's waters. Plain Language Summary: Excessive phosphorus (P) concentrations in surface water endanger public health and welfare by contributing to harmful algal blooms and hypoxic zones. Many efforts to decrease P pollution to the nation's waters have not achieved desired outcomes. To help decision‐makers develop strategies to decrease P loads, we developed an inventory of inputs and outputs of P across the United States. This inventory reveals the source and magnitude of P in a local area and how it changes through time. We found that agricultural P inputs were the largest source of P nationwide and inefficiencies in use contribute to the continued accumulation of phosphorus across the landscape. This excess phosphorus may make it more difficult to achieve water quality goals. However, many agricultural regions in the eastern and western United States demonstrated more efficient use of phosphorus fertilizer in 2012. On another positive note, urban areas in certain regions have likely decreased their fertilizer application rates, the amount of P being released by detergents, and point source loads. These efforts may have contributed to recent reports of improved water quality in more urbanized watersheds. Decision makers should consider the role of current fluxes and legacy P when designing strategies to reduce P pollution. Key Points: Agricultural surplus declined by 8% for the entire US and declines are seen in many subbasins of the eastern and western United States Atmospheric phosphorus (P) deposition increased by 9% from 2002 to 2012, coincident with increases in stream P concentrations in undisturbed watersheds Summed legacy P surplus accumulation is more than 50 times contemporary P surplus and may perpetuate eutrophication in the nation's waters